Examining the Prospects of Consociational Power Sharing as a Conflict Resolution Strategy in South Sudan. Issue 1 (2nd January 2022) - Kisaka, Michael; Nyadera, Israel; Agwanda, Billy
Abstract: South Sudan has not escaped the world's attention even after the signing of the Revitalized Agreement on the Resolution of Conflict in South Sudan (R-ARCSS) in September 2018. This agreement brought the main antagonists— President Salva Kiir and Vice-President Dr Riek Machar—to the negotiation table for the twelfth time since the conflict began in 2013. Even with the aura of a shaky peace, the main question is whether the new agreement will stand the test of time in light of the history of the failed implementation of peace agreements. This paper recognises the vital nature of the prevailing peace and examines whether consociational democracy can be propped up during this period of relative peace. The discussion hinges on consociationalism theory that contains a broad array of principles, including power sharing, requisite for consociational democracy. We argue that although South Sudan's context could favour consociational democracy, there are several barriers characterising Sudan's social and political spheres that should be alleviated. We elucidate on the barriers and suggest in broad strokes the need for strong independent institutions and vibrant civil society amongst others. We also recognise that overreliance on individuals in resolving the conflict is detrimental to the young nation, and there is a need for a citizen-centred approach that entrenches consociational principles in South Sudan's political sphere.